Designing phase I oncology dose escalation using dose-exposure-toxicity models as a complementary approach to model‐based dose-toxicity models - Kristyn Pantoja; Shankar Lanke; Alain Munafo; Anja Victor; Christina Habermehl; Armin Schueler; Karthik Venkatakrishnan; Pascal Girard; Kosalaram Goteti (Wiley, 2022)
Abstract One of the objectives of oncology phase I dose‐escalation studies has been to determine the maximum tolerated dose (MTD). Although MTD is no longer set as the dose for further development in contemporary oncology drug development, MTD determination is still important for informing the therapeutic index. Bayesian adaptive model‐based designs are becoming mainstream in oncology first‐in‐human trials. Herein, we illustrate via simulations the use of systemic exposure in Bayesian adaptive dose-toxicity models to estimate MTD. We extend traditional dose-toxicity models to incorporate pharmacokinetic exposure, which provides information on exposure-toxicity relationships. We pursue dose escalation until the maximum tolerated exposure (corresponding to the MTD) is reached. By leveraging pharmacokinetics, dose escalation considers exposure and interindividual variability on a continuous rather than discrete domain, offering additional information for dose‐escalation decisions. To demonstrate this, we generated 1000 simulations (starting dose of 1/25th the reference dose and six dose levels) for several different scenarios. Both rule‐based and model‐based designs were compared using metrics of potential safety, accuracy, and reliability. The mean results over simulations and different toxicity scenarios showed that model‐based designs were better than rule‐based methods and that exposure-toxicity model‐based methods have the potential to valuably complement dose-toxicity model‐based methods. Exposure-toxicity model‐based methods had decreased underdose risk accompanied by a relatively smaller increase in overdose risk, resulting in improved net reliability. MTD estimation accuracy was compromised when exposure variability was large, emphasizing the importance of appropriate control of pharmacokinetic variability in phase I dose‐escalation studies.